Primary Adenoid Cystic Carcinoma: An Uncommon Cause of Tracheal Obstruction - Martins,Ricardo Silva (2023)
Abstract Adenoid cystic carcinoma (ACC) of the trachea is a rare malignant neoplasm, with little consensus in the literature regarding staging and therapeutic approach. Given the rarity of trachea primary neoplasms, it is sometimes difficult to make a correct diagnosis based on clinical and imaging findings, which often results in diagnosis delays. The radiologist's familiarization with this entity is essential for early detection and inclusion in the initial differential diagnosis of mediastinal lesions, guiding the remaining diagnostic and therapeutic approach. We describe the case of a woman with clinical and imaging findings compatible with a tracheal neoplasm, that was confirmed to be an ACC. Given its longitudinal extension and the invasion of adjacent structures at diagnosis, it was considered surgically unresectable, and therefore palliative carbon-ion radiotherapy was proposed.